2022
DOI: 10.1109/access.2022.3161440
|View full text |Cite
|
Sign up to set email alerts
|

Technological Solutions for Sign Language Recognition: A Scoping Review of Research Trends, Challenges, and Opportunities

Abstract: Habitat for the Elderly, and CA19121 Network on Privacy-Aware Audio-and Video-Based Applications for Active and Assisted Living, supported by COST (European Cooperation in Science and Technology). COST (European Cooperation in Science and Technology) is a funding agency for research and innovation networks. Our Actions help connect research initiatives across Europe and enable scientists to grow their ideas by sharing them with their peers. This boosts their research, career and innovation. www.cost.eu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…Text2sign [21] HLSTM [22] ESN [23] DiffGAN [24] RG [25] SEEG [26] HA2G [27] Paul Duchnowski [28] Gérard Bailly [29] Wav2lip [30] Audio2head [31] AD-NERF [32] DiffTalk [33] Rule-based [34] LBP [35] SDF [36] PTSLP [37] Syn [38] MMFSL [39] Re-Syn [40] CMML [41] DTW [42] HMMs [43] FCN [44] RL [45] CS [1] MCCS [46] SLreview [2] UnorgSign [47] CoSreview [6] CoSreview [3] SE [48] THreview [4] THE [49] VHTHG [50] Fig. 3: Structured taxonomy of the existing BL research which includes three genres.…”
Section: Sign Language Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Text2sign [21] HLSTM [22] ESN [23] DiffGAN [24] RG [25] SEEG [26] HA2G [27] Paul Duchnowski [28] Gérard Bailly [29] Wav2lip [30] Audio2head [31] AD-NERF [32] DiffTalk [33] Rule-based [34] LBP [35] SDF [36] PTSLP [37] Syn [38] MMFSL [39] Re-Syn [40] CMML [41] DTW [42] HMMs [43] FCN [44] RL [45] CS [1] MCCS [46] SLreview [2] UnorgSign [47] CoSreview [6] CoSreview [3] SE [48] THreview [4] THE [49] VHTHG [50] Fig. 3: Structured taxonomy of the existing BL research which includes three genres.…”
Section: Sign Language Recognitionmentioning
confidence: 99%
“…SL is categorized as a natural language commonly used in deaf communities [2]. Based on data from the World Federation of the Deaf, the worldwide population of the deaf is estimated to be around 72 million, with over 80% living in developing nations [47].…”
Section: Sign Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Through using speech-to-text (STT) conversion technology, it provides a way for the hearing impaired to read a text. [1] The primary form of communication for the deaf and hard of hearing with their family members and the rest of society is sign language, which is essential in transferring meaning through a visual-manual modality. The study of sign languages has shown a new promise with the developments in computer graphics, computer vision, neural networks, and the advent of new powerful hardware.…”
Section: Introductionmentioning
confidence: 99%
“…A review of CSLR literature [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] reveals a growing body of research focused on developing robust and efficient recognition systems. However, no work related to CSLR with intonation-colored speech has been carried out for the Kazakh language.…”
Section: Introductionmentioning
confidence: 99%